2013
DOI: 10.1534/genetics.113.154583
|View full text |Cite
|
Sign up to set email alerts
|

Spargel/dPGC-1 Is a New Downstream Effector in the Insulin–TOR Signaling Pathway in Drosophila

Abstract: Insulin and target of rapamycin (TOR) signaling pathways converge to maintain growth so a proportionate body form is attained. Insufficiency in either insulin or TOR results in developmental growth defects due to low ATP level. Spargel is the Drosophila homolog of PGC-1, which is an omnipotent transcriptional coactivator in mammals. Like its mammalian counterpart, Spargel/dPGC-1 is recognized for its role in energy metabolism through mitochondrial biogenesis. An earlier study demonstrated that Spargel/dPGC-1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 40 publications
4
32
0
2
Order By: Relevance
“…In a recent report TOR signaling was found to function as a positive regulator of PGC-1/ srl in growth process during larval development of Drosophila (Mukherjee and Duttaroy, 2013), which is consistent with previous findings that PGC-1/ srl -deficient Drosophila larvae exhibit dramatic growth impairment (Tiefenbock et al, 2010). In contrast, however, we provided strong evidence in this study that during metabolic homeostasis in the adult animal, PGC-1/ srl is a negative effector of HFD-induced augmentation of TOR signaling.…”
Section: Discussionsupporting
confidence: 90%
“…In a recent report TOR signaling was found to function as a positive regulator of PGC-1/ srl in growth process during larval development of Drosophila (Mukherjee and Duttaroy, 2013), which is consistent with previous findings that PGC-1/ srl -deficient Drosophila larvae exhibit dramatic growth impairment (Tiefenbock et al, 2010). In contrast, however, we provided strong evidence in this study that during metabolic homeostasis in the adult animal, PGC-1/ srl is a negative effector of HFD-induced augmentation of TOR signaling.…”
Section: Discussionsupporting
confidence: 90%
“…Future studies will therefore be important to confirm whether the sex-specific regulation of bmm mRNA under normal culture conditions and post-starvation occurs via IIS and Foxo. Furthermore, it will be important to test whether additional nutrient-responsive pathways contribute to the sex-specific regulation of bmm and the male-female difference in triglyceride storage, such as the adipokinetic hormone (AKH; FBgn0004552) pathway [68,83,84], the sterol response element binding protein (SREBP; FBgn0261283) pathway [85,86], and spargel/peroxisome proliferator-activated receptor γ coactivator 1 (srl/PGC-1; FBgn0037248) pathway [87,88], as much of our knowledge of these pathways is derived from studies using either a mixed-sex population of larvae or adult male flies. Another possible explanation for the sex differences in triglyceride homeostasis is that sex determination genes directly establish a "male" or a "female" metabolic state via regulation of triglyceride metabolism genes such as bmm.…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that a Spargel-GFP fusion protein also localizes itself in the nucleus forming distinct punctate structures (Mukherjee and Duttaroy, 2013). An authentic Nuclear Localization Signal (NLS) was uncovered in Spargel/dPGC-1 with the help of a NLS predict software (Mukherjee and Duttaroy, 2013) that most likely assists in Spargel/dPGC-1 localization into the nucleus.…”
Section: Intracellular Localizationmentioning
confidence: 99%
“…Spargel/dPGC-1 is a terminal effector of this pathway hence reduced spargel expression results in growth retardation with smaller body size and developmental delays, though Spargel/dPGC-1 overexpression has no immediate effect on growth (Rera et al, 2011; Mukherjee and Duttaroy, 2013). …”
Section: Growth Longevity and Agingmentioning
confidence: 99%